2012
DOI: 10.4049/jimmunol.1101651
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C-θ Is Required for Murine Neutrophil Recruitment and Adhesion Strengthening under Flow

Abstract: Protein kinase C (PKC)-θ is involved in T cell activation via regulating the avidity of the β2 integrin LFA-1 in the immunological synapse. LFA-1 also mediates leukocyte adhesion. To investigate the role of PKC-θ in neutrophil adhesion, we performed intravital microscopy in cremaster venules of mice reconstituted with bone marrow from LysM-GFP+ (wild-type [WT]) and PKC-θ gene-deficient (Prkcq−/−) mice. Following stimulation with CXCL1, both WT and Prkcq−/− cells became adherent. Although most WT neutrophils re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 51 publications
0
30
2
1
Order By: Relevance
“…Phospholipase C signaling downstream of LFA-1 has been reported to be important for firm adhesion of effector T cells (10). PKC/protein kinase D (PKD) signaling are downstream of phospholipase C in cells, and PKC isoforms have recently been implicated in neutrophil adhesion strengthening under conditions of shear flow (17). However, effector T cell adhesion to ICAM-1 under shear flow conditions is independent of PKC (this report), and we have previously reported that it is also independent of PKD (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phospholipase C signaling downstream of LFA-1 has been reported to be important for firm adhesion of effector T cells (10). PKC/protein kinase D (PKD) signaling are downstream of phospholipase C in cells, and PKC isoforms have recently been implicated in neutrophil adhesion strengthening under conditions of shear flow (17). However, effector T cell adhesion to ICAM-1 under shear flow conditions is independent of PKC (this report), and we have previously reported that it is also independent of PKD (9).…”
Section: Discussionmentioning
confidence: 99%
“…Phospholipase C activity has previously been implicated in LFA-1 regulation in human effector T cells (10), and this enzyme is upstream of protein kinase C (PKC) activation in cells. PKC isoforms have been implicated in LFA-1 adhesion under flow in T cells and neutrophils (16,17). We therefore used the general PKC inhibitor, Ro-318220, to investigate the dependence of effector T cell adhesion under shear flow on PKC activity.…”
Section: Lfa-1-mediated Adhesion Of Effector T Cells Under Flow Condimentioning
confidence: 99%
“…Conversely, the number of adherent neutrophils increases. For stable neutrophil adhesion, additional signaling steps are needed that depend on integrin outside-in signaling (16, 17), provided by both αMβ2 (Mac-1) and αLβ2 (LFA-1).…”
Section: Introductionmentioning
confidence: 99%
“…Since alterations in adhesion forces, cell spreading and membrane tension have been reported as being responsible for defective cell migration [23][24][25][26], we tested the ability of Myo1g-deficient B cells to migrate toward a chemokine gradient. We used CXCL13 to induce migration of resting B lymphocytes over a fibronectincoated surface in a chemotaxis chamber.…”
Section: Slow B-cell Migration In Vitro and Defective Homing In Vivomentioning
confidence: 99%